(untitled) (Journal of Educational Sciences, 2016)
Future shape and condition of the Kazakh as multicultural and secular society, largely depends on the level of tolerance and interfaith relations. The problem of tolerance is particularly relevant in terms of the bundle of society on economic, social and other features, and the associated rise in intolerance, terrorism, religious extremism, development and aggravation of interethnic relations. The study was conducted at the Scientific–research Institute of social and educational research A. Myrzakhmetov Kokshetau University in December 2013, among the students of the specialty «Psychology» of the third and fourth courses of the two universities in the number of 30 people. The purpose of this article is to identify the levels of religious consciousness and tolerance of the students. The article presents an analysis of empirical research data obtained by focus of the groups and observation. Revealed that one in three respondents admitted that religion plays a crucial role in their lives as an internal value–rod; tolerant attitude to all world religions; factors effective prevention among students. Tolerance as significant value is formed in the mind of the student in the space of respect for dissent and different faith based on the knowledge of otherness in the sphere of religion. The formation of a tolerant life style and thinking is also associated with education through mass media on the issue of religion. Social support for students from the state creates a healthy image of the student, which generates a strong immunity to the antisocial including religious–extremist nature.